Electron transport layer of solar cell and method of manufacturing solar cell

The electron transport layer with a carboxyl-group-containing ammonium salt surface treatment film addresses surface defects and crystal deterioration in perovskite solar cells, enhancing durability and efficiency by forming a two-dimensional perovskite structure.

JP2024176491AInactive Publication Date: 2024-12-19AISIN CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023095051
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-08
Publication Date
2024-12-19
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing perovskite solar cells suffer from surface defects and crystal deterioration in the perovskite layer, leading to reduced conversion efficiency and durability due to incomplete surface treatment and limited crystal growth strategies.

Method used

An electron transport layer with a surface treatment film containing tertiary or quaternary ammonium salts with carboxyl groups is applied to the perovskite layer, forming a two-dimensional structure that stabilizes the crystal surface and suppresses electron-hole recombination.

Benefits of technology

The solution enhances the durability and conversion efficiency of perovskite solar cells by improving the surface defects and charge balance, resulting in improved stability and performance over time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176491000001_ABST
    Figure 2024176491000001_ABST
Patent Text Reader

Abstract

To provide an electron transport layer for a perovskite solar cell, which improves surface defects of the perovskite layer, improves the conversion efficiency of the device, and enhances durability.SOLUTION: An electron transport layer 3 for transporting electrons between the electron transport layer 3 and a perovskite layer 4 of a solar cell 10, and on a surface treatment film 34 formed on the surface of the electron transport layer 3 in contact with the perovskite layer 4, a surface treatment film 34 including a tertiary or quaternary ammonium salt having a carboxyl group is formed.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electron transport layer for a solar cell and a method for producing the same. [Background technology]

[0002] Solar cells generally use elements such as silicon, compound semiconductors, and organic semiconductors, but hybrid solar cells (perovskite solar cells) are attracting attention because of their high light-harvesting ability and the ability to be made thin and reduce costs.

[0003] Non-Patent Document 1 discloses a pin-structure perovskite solar cell including a glass substrate with a transparent conductive film, a hole transport layer, a perovskite layer made of methylamine lead iodide (CH3NH3PbI3: hereinafter sometimes abbreviated as "MAPbI3"), an electron transport layer, a buffer layer, an electron transport layer, and an electrode.

[0004] In such solar cells, the perovskite layer is formed as a polycrystalline thin film. Generally, polycrystalline thin films have surface defects and crystal grain boundaries, which cause recombination of holes and electrons in the perovskite layer, resulting in a decrease in the conversion efficiency of the solar cell device and deterioration of the crystal. Therefore, in Non-Patent Document 1, after forming the perovskite layer, the upper surface of the perovskite layer is surface-treated using n-butylamine or n-butylammonium iodide, and the perovskite compound is arranged two-dimensionally on the crystal surface and crystal grain boundaries, thereby improving the conversion efficiency and durability of the device. It has been reported that the conversion efficiency has improved from 17.3% to 19.3%.

[0005] Non-Patent Document 2 discloses a perovskite solar cell with an ni-p structure in which a monomolecular film made of glycine hydroiodide, β-alanine hydroiodide, or γ-aminobutyric acid hydroiodide is formed on the surface of an electron transport layer made of porous titanium dioxide (TiO2), and a perovskite layer made of MAPbI3 is formed on top of the monomolecular film.

[0006] It has been reported that in this solar cell, some of the glycine hydroiodide salts present on the electron transport layer penetrate into the A site of the perovskite compound at the interface with the perovskite layer, promoting the crystal growth of the perovskite compound. This improves surface defects on the underside of the perovskite layer, improving the conversion efficiency from 8% to 10%. [Prior art documents] [Non-patent literature]

[0007] [Non-Patent Document 1] Yun Lin et al., “Enhanced Thermal Stability in Perovskite SolarCells by Assembling 2D / 3D Stacking Structures”, J. Phys. Chem. Lett. 2018, 9, 654-658 (DOI: 10.1021 / acs.jpclett.7b02679) [Non-Patent Document 2] Yuhei Ogami et al., “All-Solid Perovskite Solar Cells with HOCO-R-NH3+I- Anchor-Group Inserted between Porous Titania and Perovskite”, J. Phys. Chem. C 2014, 118, 30, 16651-16659 (DOI: 10.1021 / jp412627n) Summary of the Invention [Problem to be solved by the invention]

[0008] Since the surface treatment in Non-Patent Document 1 is performed after the formation of the perovskite layer, the lower surface of the perovskite layer located at the interface between the hole transport layer and the perovskite layer is not surface-treated, and therefore surface defects still exist on the lower surface of the perovskite compound.

[0009] In addition, in Non-Patent Document 2, crystal growth is performed between the electron transport layer and the perovskite layer via a monolayer, and surface defects may occur due to crystal decomposition of the perovskite compound. Therefore, there is room for improvement in the defects on the crystal surface.

[0010] Therefore, there is a demand for an electron transport layer for perovskite solar cells that improves the surface defects of the perovskite layer, which is a polycrystalline thin film, thereby improving the device's conversion efficiency and durability. [Means for solving the problem]

[0011] The electron transport layer according to the present invention is characterized in that the electron transport layer transports electrons between the electron transport layer and the perovskite layer of a solar cell, and a surface treatment film containing a tertiary or quaternary ammonium salt having a carboxyl group is formed on the surface of the electron transport layer that is in contact with the perovskite layer.

[0012] On the surface of the electron transport layer in contact with the perovskite layer, a monomolecular film of a tertiary or quaternary ammonium salt having a carboxyl group is formed as a surface treatment film. In this surface treatment film, the carboxyl group is adsorbed on the surface of the electron transport layer. Since the side chain of the ammonium salt opposite to the carboxyl group is positively charged, it is easy to attract the anion of the perovskite compound formed on the surface treatment film. However, since the ammonium group according to the present invention is tertiary or quaternary and bulky, the perovskite compound cannot incorporate the ammonium group into the A site in the three-dimensional structure. Therefore, it is considered that the perovskite compound cannot form a three-dimensional structure on the surface treatment film and reacts with the ammonium salt to form a two-dimensional structure. Since a three-dimensional crystal of the perovskite compound is formed on this two-dimensional structure, the perovskite layer has a two-dimensional structure on its surface. The three-dimensional crystals of perovskite compounds, which have a two-dimensional structure, have stabilized crystal surfaces, which improves the durability of solar cells and suppresses the recombination of holes and electrons caused by defects in the perovskite layer, thereby improving the conversion efficiency.

[0013] In addition, the ammonium groups become more easily charged, which stabilizes the charge balance in the crystal lattice of the perovskite layer, and nucleation occurs more easily, which improves the quality of the perovskite layer. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a schematic cross-sectional view of a perovskite solar cell. [Diagram 2] FIG. 1 is an explanatory diagram of power generation in a perovskite solar cell. [Diagram 3] FIG. 1 is an explanatory diagram showing a procedure for producing a perovskite solar cell. [Figure 4] FIG. 2 is a comparative diagram showing performance curves of Example 1, Example 2, and a comparative example. [Diagram 5] FIG. 2 is a comparative diagram showing performance curves of Example 1, Example 2, and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, an embodiment of the electron transport layer according to the present invention will be described with reference to the drawings. In this embodiment, an electron transport layer of a perovskite solar cell will be described as an example of the electron transport layer. However, the present invention is not limited to the following embodiment, and various modifications are possible within the scope of the present invention.

[0016] [Basic configuration of the solar cell according to this embodiment] As shown in FIG. 1, the solar cell 10 according to this embodiment includes a substrate 2 having a transparent substrate 21 and a transparent conductive film 22, an electron transport layer 3, a perovskite layer 4, a hole transport layer 5, and an electrode 6, which are sequentially formed into a laminate 11. The electron transport layer 3 is composed of a dense layer 32 and a porous layer 33, and transfers electrons to the transparent conductive film 22, and separates the hole transport layer 5 from the transparent conductive film 22 to prevent recombination of electrons and holes (reverse electron transfer). The electrons transferred to the transparent conductive film 22 move to a photoelectrode 61 provided on the surface of the transparent conductive film 22. A surface treatment film 34 is provided on the surface of the porous layer 33. The perovskite layer 4 is provided on the surface treatment film 34, and is excited by light to generate electrons. The hole transport layer 5 transports holes generated in the perovskite layer 4 to a counter electrode 62 provided on the surface of the hole transport layer 5. The electrons emitted from the photoelectrode 61 are received by the counter electrode 62. The arrangement of the electrode 6 is not particularly limited as long as it is capable of transferring electrons, for example, by connecting a conductor to the electron transport layer 3 to form a photoelectrode 61. In order to increase the durability of the solar cell 10, the counter electrode 62 may be protected by a transparent substrate 21 or the like.

[0017] The transparent substrate 21 is made of a material having optical transparency. For example, a transparent glass substrate, a frosted semi-transparent glass substrate, a transparent resin substrate, etc. can be used. For the transparent conductive film 22, for example, fluorine-doped tin oxide (FTO), tin oxide (TO), tin-doped indium oxide (ITO), zinc oxide (ZnO), aluminum-doped zinc oxide (AZO), etc. can be used.

[0018] Metal oxides are suitable for the electron transport layer 3 consisting of the dense layer 32 and the porous layer 33. For example, titanium dioxide (TiO2), zinc oxide (ZnO), niobium oxide (Nb2O5), tin dioxide (SnO2), aluminum oxide (Al2O3), etc. are used. In particular, it is preferable to configure it as a sintered body of titanium dioxide (TiO2) that can secure a large surface area for stacking the perovskite layer 4. In addition, the dense layer 32 is formed by extending a part into the transparent conductive film 22, partitioning the transparent conductive film 22 and forming the insulating layer 31. In the dense layer 32, electrons can pass through in the stacking direction, but the insulating layer 31 suppresses the movement of electrons in the lateral direction. In other words, the electrons that have entered from the electron transport layer 3 move smoothly in the stacking direction of the transparent conductive film 22 and are supplied to the photoelectrode 61, and the movement to the counter electrode 62 is prevented by the insulating layer 31, so that no short circuit occurs.

[0019] The ammonium salt constituting the surface treatment film 34 may be a tertiary ammonium having a carboxyl group represented by Chemical Formula 1 or a quaternary ammonium having a carboxyl group represented by Chemical Formula 2. The tertiary ammonium is represented by R 2 , R 3 A-C n H 2n+1 (n is an integer from 1 to 4), R 4 A-C m H 2m - (m is an integer from 1 to 5). 2 and R 3 may be the same or different. In addition, for quaternary ammonium, R 1 , R 2 , R 3 A-C n H 2n+1 (n is an integer from 1 to 4), R 4 A-C m H 2m - (m is an integer from 1 to 5). 1 , R 2 , R 3may be the same or different. As the ammonium salt, for example, a hydrogen halide salt may be used. As the halogen element, for example, chlorine, bromine, iodine, etc. may be used. The ammonium salt is not limited to a hydrogen halide salt, and may be a carbonate salt or a nitrate salt.

[0020] [ka] [ka]

[0021] Quaternary ammonium R 1 and R for tertiary or quaternary ammonium 2 , R 3 -C in n H 2n+1 is an alkyl group, whether linear or branched. The chain length is not particularly limited as long as the number of carbon atoms constituting the alkyl group is 1 to 4. Specific examples include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, an s-butyl group, and a t-butyl group.

[0022] R 4 -C in m H 2m - is an alkylene group, whether linear or branched. The chain length is not particularly limited as long as the number of carbon atoms constituting the alkylene group is 1 to 5. Specific examples include a methylene group, a methylmethylene group, an ethylene group, a trimethylene group, a 1-methylethylene group, a tetramethylene group, a 1-methyltrimethylene group, a 2-methyltrimethylene group, a 3-methyltrimethylene group, a 1-methylpropylene group, a 1,1-dimethylethylene group, a pentamethylene group, a 1-methyltetramethylene group, a 2-methyltetramethylene group, a 3-methyltetramethylene group, a 4-methyltetramethylene group, a 1,1-dimethyltrimethylene group, a 2,2-dimethyltrimethylene group, and a 3,3-dimethyltrimethylene group.

[0023] The perovskite layer 4 is produced by reacting a compound (PbX2, X = halogen element) composed of lead and halogen element X with methylammonium iodide (CH3NH3I: hereinafter sometimes abbreviated as "MAI"). Specifically, a solution containing lead and halogen element X is infiltrated into the inside of the pores of the porous layer 33 on which the surface treatment film 34 is formed, dried, and then immersed in a mixed solution of MAI to rapidly produce crystals of the perovskite compound (CH3NH3PbI3 when X = I) that forms the perovskite layer 4. Although iodine, bromine, chlorine, etc. can be used as the halogen element X, it is preferable to use iodine, which has high morphological stability. In addition, a mixed cation-mixed halide ((FAPbI3)) using MABr, 0.2M lead bromide (PbBr2), formamidine hydroiodide (CH4N2·HI: hereinafter sometimes abbreviated as "FAI"), and lead iodide (PbI2) was also produced. 1-x (MAPbBr3) x ) can also be used. For example, (FAPbI3) 0.85 (MAPbBr3) 0.15 etc. can be suitably used.

[0024] The hole transport layer 5 may be made of a spirobifluorene compound (spiro-OMeTAD), poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) (PTAA), etc. The electrode 6 may be made of, for example, a simple metal or alloy of gold, platinum, silver, copper, etc., or an oxide conductor such as fluorine-doped tin oxide (FTO) or tin-doped indium oxide (ITO).

[0025] Next, the principle of how the solar cell 10 generates electricity will be described with reference to FIG. 2. When light such as sunlight or room light is incident on the transparent substrate 21, the incident light is hardly absorbed and passes through the substrate 2 and the electron transport layer 3, and most of the incident light reaches the perovskite layer 4. When the incident light is irradiated onto the perovskite layer 4, the perovskite layer 4 absorbs the light energy and becomes excited. When the energy level of the perovskite layer 4 becomes higher than the conduction band potential of the metal oxide that is the porous layer 33 of the electron transport layer 3 by a predetermined level or more due to this excitation, electrons are injected from the perovskite layer 4 into the porous layer 33. The injected electrons are collected by the photoelectrode 61 via the dense layer 32.

[0026] On the other hand, holes generated in the perovskite layer 4 reach the counter electrode 62 via the hole transport layer 5, where they recombine with electrons that have passed through the external load 7. In other words, a potential gradient is generated between the photoelectrode 61 and the counter electrode 62, and therefore, by connecting the external load 7 between the two electrodes, electricity can be generated.

[0027] [Procedure for producing the solar cell according to this embodiment] Next, a procedure for producing the solar cell 10 according to this embodiment will be described with reference to FIG. 3. However, the present invention is not limited to the following embodiment, and various modifications are possible without departing from the spirit of the invention. The solar cell 10 can be produced with reference to known techniques such as those described in Michael Saliba et al., “Correction to “How to Make over 20% Efficient Perovskite Solar Cells in Regular (nip) and Inverted (pin) Architectures”, Chem. Mater., 2018, 30, 4193-4218.

[0028] First, the transparent conductive film 22 is formed on the transparent substrate 21 to prepare the substrate 2. The transparent conductive film 22 is laminated on the transparent substrate 21 by, for example, CVD (chemical vapor deposition) or sputtering. Next, the transparent conductive film 22 is partially removed by laser scribing to form a recess 221 for the insulating layer 31, and then washed. Next, a dense layer 32 is formed on the entire surface of the substrate 2 by ALD (atomic layer deposition) or SPD (spray pyrolysis). The dense layer 32 is preferably formed as a TiO2 dense layer. Next, a porous layer 33, which is a nanoparticle sintered layer, is formed near the center of the masked substrate 2 and dense layer 32. It is preferably formed as a TiO2 porous layer 33 (p-TiO2). This porous layer 33 is formed by diluting the nanoparticle paste with a solvent, applying it by spin coating at a rotation speed of, for example, 4000 rpm to 6000 rpm, drying it, removing the masking, and heating it at 450° C. to 550° C. to sinter it.

[0029] Next, for example, an ethanol solution of (carboxymethyl)trimethylammonium hydrochloride (hereinafter sometimes referred to as betaine hydrochloride) is prepared, and the porous layer 33 is immersed in this solution and dried to form a surface treatment film 34 on the surface of the porous layer 33.

[0030] Next, for example, a solution of PbI2 in N,N-dimethylformamide is prepared and dropped onto the porous layer 33, and then, for example, the solution is permeated into the pores (p-TiO2) and excess solution is removed by spin coating at a rotation speed of 5000 rpm to 8000 rpm. The solution is dried at 60°C to 120°C (preferably 70°C to 90°C) to form a PbI2 layer.

[0031] The substrate 2, dense layer 32, and porous layer 33 permeated with lead iodide are immersed in an isopropyl alcohol solution (2-20mg / ml) of MAI (CH3NH3I) at 0°C to 80°C (preferably at room temperature) (MAI immersion method). PbI2 and MAI react to form a perovskite compound [(CH3NH3)PbI3(MAPbI3)] as a perovskite layer 4 inside and on the pores of the porous layer 33, and then the porous layer is flooded with a pure isopropyl alcohol solution and dried at 60°C to 120°C (preferably 70°C to 100°C). The mixed cation-mixed halide ((FAPbI3) 1-x (MAPbBr3) x ) type perovskite compounds can be prepared in a similar manner.

[0032] The hole transport material according to the present embodiment is prepared as, for example, a chlorobenzene solution of 60 to 90 mg / ml. The solution is dropped onto the perovskite layer 4, and excess solution is removed by spin coating, followed by drying to form the hole transport layer 5. An additive such as 4-isopropyl-4'-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate (TPFB) may be added to the hole transport material. When TPFB is added, the TPFB is preferably 0.01% by weight to 100% by weight of the hole transport material, and particularly preferably 0.1% by weight to 50% by weight. For example, the hole transport material according to the present embodiment is weighed out to be 30 mM, and TPFB equivalent to 10% by weight is added thereto, and the resulting solution is dissolved in chlorobenzene to form the hole transport layer 5.

[0033] The steps from forming the PbI2 layer to forming the hole transport layer 5 are preferably carried out in a dry nitrogen atmosphere such as in a glove box. Finally, a thin film of gold or the like is attached to the surfaces of the electron transport layer 3 and the hole transport layer 5 by a method such as vacuum deposition to form an electrode 6.

[0034] In the above-mentioned manufacturing procedure, the crystal growth of the perovskite compound forming the perovskite layer 4 is controlled in two steps, but this may be performed in one step. For example, a perovskite ((CH3NH3)PbI3) solution is permeated into the pores of the porous layer 33 by spin coating. Toluene is dropped during spinning to precipitate microcrystals and make the surface mirror-finished (poor solvent precipitation method). Then, the hole transport layer 5 may be formed from the hole transport material according to this embodiment.

[0035] [Preferable examples of surface treatment film materials according to this embodiment] A suitable example of the tertiary ammonium salt having a carboxyl group according to this embodiment is 3-(diethylamino)propionohydrochloride.A suitable example of the quaternary ammonium salt having a carboxyl group is betaine hydrochloride.

[0036] [Characteristics of the surface treatment film according to this embodiment] In the surface treatment film 34 according to this embodiment, the carboxyl group is adsorbed on the metal oxide surface forming the electron transport layer 3. Since the molecules constituting the surface treatment film 34 have a linear structure, the ammonium salt is arranged perpendicular to the electron transport layer 3. Then, the positively charged ammonium group is present on the upper surface of the surface treatment film 34, so that in the process of forming the perovskite layer 4, the perovskite compound reacts with the ammonium salt. Since the perovskite compound has anions consisting of lead and halogen element X and cations such as MA, the anions are attracted to the ammonium salt on the surface treatment film 34. Here, since the ammonium salt is tertiary or quaternary, it is bulky and cannot enter the A site in the crystal lattice of the perovskite compound having a three-dimensional structure. Therefore, on the surface treatment film 34, the perovskite compound does not have a three-dimensional structure but has a two-dimensional structure. When a three-dimensional crystal is formed on the perovskite compound having such a two-dimensional structure, defects on the crystal surface can be reduced, and the solar cell performance is improved.

[0037] The present invention will now be described in detail with reference to the following examples.

[0038] [Example] As an example, fluorine-doped tin oxide (FTO) glass (23 mm x 14 mm x 1.6 mm) was used for the transparent substrate 21. This FTO glass was laser scribed to form a recess 221 by removing the FTO, and was thoroughly washed. Next, a TiO2 dense film was formed as the dense layer 32 by spray pyrolysis (SPD). Furthermore, a solution of commercially available TiO2 nanoparticle paste diluted with ethanol was dropped, applied by spin coating, and dried at 100°C. After drying, the substrate was baked at 450°C to form a TiO2 nanoparticle layer that would become the porous layer 33. After baking, the substrate was cooled to room temperature.

[0039] Next, a treatment solution was prepared for forming the surface treatment film 34 on the surface of the porous layer 33. First, betaine hydrochloride was weighed and dehydrated ethanol was poured into it. Next, this solution was ultrasonically treated to completely dissolve the betaine hydrochloride, and a treatment solution was prepared. In addition, a similar treatment was carried out using 3-(diethylamino)propionyl hydrochloride instead of betaine hydrochloride, to prepare a treatment solution.

[0040] After the porous layer 33 was immersed in each of the above-mentioned treatment solutions for 30 minutes, it was rinsed with dehydrated ethanol and then dried by nitrogen blowing.

[0041] Next, a perovskite precursor solution for forming the perovskite layer 4 was prepared. First, FAI (CH(NH2)2I) was weighed out, and a 1.7M solution of PbI2 / dimethylformamide (DMF) + dimethyl sulfoxide (DMSO) that had been prepared in advance was poured into it to prepare a FAPbI3 solution. Next, MAI (CH3NH3I) was weighed out, and a 1.7M solution of PbI2 / dimethylformamide (DMF) + dimethyl sulfoxide (DMSO) that had been prepared in advance was poured into it to prepare a MAPbI3 solution.

[0042] Finally, the FAPbI3 solution, the MAPbI3 solution, and a previously prepared 1.7 M CsI / dimethyl sulfoxide (DMSO) solution were mixed to prepare a precursor solution to be subjected to spin coating.

[0043] The perovskite layer 4 was formed by dropping the precursor solution onto the porous layer 33 on which the surface treatment film 34 was formed, and applying the solution by spin coating. After application was completed, the solution was heated at 100° C. for 60 minutes, and then cooled to room temperature.

[0044] Next, the hole transport layer 5 was prepared. As the hole transport material, 2,2',7,7'-tetrakis-(N,N-di-methoxyphenylamine)-9,9'-spirobifluorene (Spiro-OMeTAD) was used. The hole transport material solution was weighed out to a final concentration of 60 mM and dissolved in chlorobenzene. Next, lithium trifluoromethanesulfonylimide (LiTFSI) equivalent to 50 mol% of the hole transport material and 4-tert-butylpyridine (TBP) equivalent to 350 mol% were added to the above-mentioned solution to prepare a hole transport material solution. Note that the cobalt complex (FK209), which is commonly used as a dopant, was not added. The hole transport layer 5 was formed by dropping the hole transport material solution onto the perovskite film and forming it by a spin coating method.

[0045] After the hole transport layer 5 was formed, a gold film of about 100 nm was formed by vacuum deposition, which was then removed to form the electrode 6, which was then laminated.

[0046] Next, the performance of the solar cell 10 was evaluated. Here, the solar cell 10 was fabricated and examined for one in which the surface treatment film 34 was formed on the surface of the porous layer 33 using betaine hydrochloride (Example 1), one in which the surface treatment film 34 was formed using 3-(diethylamino)propionyl hydrochloride (Example 2), and one in which the surface treatment film 34 was not formed (Comparative Example).

[0047] Table 1 shows the results of the cell performance evaluation of solar cell 10. Table 1 summarizes the parameters of solar cell 10, including the short circuit current density (hereinafter sometimes referred to as "Jsc"), open circuit voltage (hereinafter sometimes referred to as "Voc"), fill factor (hereinafter sometimes referred to as "FF"), and conversion efficiency (hereinafter sometimes referred to as "PCE"). FF is the maximum output P at the point where the product of current and voltage is maximum. max is calculated by dividing by (Voc × Jsc), and PCE is calculated by (Voc × Jsc × FF ÷ incident light intensity).

[0048] [Table 1]

[0049] From the results in Table 1, Example 1 using betaine hydrochloride and Example 2 using 3-(diethylamino)propionyl hydrochloride had PCE of 17.0%, which showed higher solar cell characteristics compared to the PCE of 15.8% for the comparative example in which the surface treatment film 34 was not formed. It was found that the cell performance changed depending on the difference in the molecular shape constituting the surface treatment film 34.

[0050] Fig. 4 shows a current-voltage curve measured immediately after the fabrication of the solar cell 10, and Fig. 5 shows a current-voltage curve measured one month after the fabrication of the solar cell 10. In Examples 1 and 2, the curves do not change over time, whereas in the comparative example in which the surface treatment film 34 is not formed, the current value one month after fabrication decreases, indicating that the device is not stable. Therefore, it was found that the durability of the solar cell 10 is improved by providing the surface treatment film 34 on the surface of the electron transport layer 3.

[0051] In the above-described embodiment, the following configurations are envisaged. (1) An electron transport layer 3 that transports electrons between the electron transport layer 3 and the perovskite layer 4 of a solar cell 10, the electron transport layer 3 having a surface treatment film 34 formed on the surface of the electron transport layer 3 that contacts the perovskite layer 4, the surface treatment film 34 containing a tertiary or quaternary ammonium salt having a carboxyl group.

[0052] When a surface treatment film 34 containing a tertiary or quaternary ammonium salt having a carboxyl group is formed on the surface of the electron transport layer 3 in contact with the perovskite layer 4, the carboxyl group is adsorbed on the surface of the porous layer 33. The side chain of the ammonium salt opposite to the carboxyl group is positively charged, so it is easy to attract anions of the perovskite compound formed on the surface treatment film 34. However, since the ammonium group according to the present invention is tertiary or quaternary and bulky, the perovskite compound cannot incorporate the ammonium group into the A site in the three-dimensional structure. Therefore, it is considered that the perovskite compound cannot form a three-dimensional structure on the surface treatment film 34 and reacts with the ammonium salt to form a two-dimensional structure. Since a three-dimensional crystal of the perovskite compound is formed on this two-dimensional structure, the perovskite layer 4 has a two-dimensional structure on its surface. The three-dimensional crystals of the perovskite compound having a two-dimensional structure have a stabilized crystal surface, which improves the durability of the solar cell 10 and suppresses the recombination of holes and electrons caused by defects in the perovskite layer 4, thereby improving the conversion efficiency.

[0053] (2)(1) The surface treatment film 34 preferably contains a quaternary ammonium salt having a carboxyl group.

[0054] As the number of substituents introduced to the N atoms increases, the ammonium groups become bulkier, making it more difficult for them to enter the A site in the three-dimensional structure of the perovskite compound. Therefore, the perovskite compound is more likely to have a two-dimensional structure at the interface between the perovskite layer 4 and the surface treatment film 34. Furthermore, as the number of substituents introduced to the N atoms increases, the ammonium groups become more easily charged, stabilizing the charge balance of the perovskite compound at the interface of the perovskite layer 4.

[0055] (3)(1) The surface treatment film 34 preferably contains a betaine hydrohalide salt.

[0056] Betaine hydrogen halide salts are widely available on the market and are inexpensive, making it possible to provide a high-performance electron transport layer 3 without increasing manufacturing costs. In addition, if the alkyl group bonded to the ammonium group forming the surface treatment film 34 is long, it becomes difficult to form the perovskite layer 4 on the surface treatment film 34, so betaine hydrogen halide salts having an ammonium group bonded to a short alkyl group are suitable.

[0057] (4) A method for manufacturing a solar cell 10, which sequentially includes the steps of forming a transparent conductive film 22 on a transparent substrate 21, forming an electron transport layer 3, forming a surface treatment film 34 containing a tertiary or quaternary ammonium salt having a carboxyl group on the electron transport layer 3, forming a perovskite layer 4 on the surface treatment film 34, forming a hole transport layer 5, and forming an electrode 6.

[0058] By going through the above steps, the surface treatment film 34 is formed on the underside of the perovskite layer 4, so that surface defects of the perovskite layer 4 are improved, and a solar cell 10 with improved conversion efficiency and durability can be obtained.

[0059] Other embodiments (1) In the above-described embodiment, as reported in Non-Patent Document 1, after the formation of the perovskite layer 4, a monomolecular film may be formed on the surface of the perovskite layer 4. This produces a two-dimensional structure of the perovskite compound on the upper and lower surfaces of the three-dimensional crystal of the perovskite layer 4, thereby improving the stability of the crystal surface.

[0060] (2) In the above-described embodiment, a compound containing lead is given as a perovskite compound, but instead of lead, a perovskite compound containing tin (Sn), zinc (Zn), titanium (Ti), germanium (Ge), etc. may be used. Moreover, instead of MA and FA, an organic molecular cation, which is a monovalent cation, or an alkali metal cation may be used. [Industrial Applicability]

[0061] The present invention can be used in the electron transport layer used in perovskite solar cells comprising perovskite compounds formed from organic and inorganic hybrid compounds. [Explanation of symbols]

[0062] 10: solar cell, 2: substrate, 22: transparent conductive film, 3: electron transport layer, 34: surface treatment film, 4: perovskite layer, 5: hole transport layer, 6: electrode

Claims

1. An electron transport layer through which electrons are transported to and from a perovskite layer of a solar cell, an electron transport layer, the surface of which is in contact with the perovskite layer, and on which a surface treatment film containing a tertiary or quaternary ammonium salt having a carboxyl group is formed;

2. The electron transport layer according to claim 1 , wherein the surface treatment film contains a quaternary ammonium salt having a carboxyl group.

3. The electron transport layer according to claim 2 , wherein the surface treatment film contains a betaine hydrohalide salt.

4. forming a transparent conductive film on a substrate; forming an electron transport layer; forming a surface treatment film containing a tertiary or quaternary ammonium salt having a carboxyl group on the electron transport layer; forming a perovskite layer on the surface treatment film; forming a hole transport layer; and forming an electrode.